Mechanism of Action of Mesenchymal Stem Cell-Derived Exosomes in the Intervertebral Disc Degeneration Treatment and Bone Repair and Regeneration - Liang, Weishi; Han, Bo; Hai, Yong; Sun, Duan; Yin, Peng (Frontiers in Cell and Developmental Biology, 2022)
Exosomes are extracellular vesicles formed by various donor cells that regulate gene expression and cellular function in recipient cells. Exosomes derived from mesenchymal stem cells (MSC-Exos) perform the regulatory function of stem cells by transporting proteins, nucleic acids, and lipids. Intervertebral disc degeneration (IDD) is one of the main causes of low back pain, and it is characterized by a decreased number of nucleus pulposus cells, extracellular matrix decomposition, aging of the annulus fibrosus, and cartilage endplate calcification. Besides, nutrient transport and structural repair of intervertebral discs depend on bone and cartilage and are closely related to the state of the bone. Trauma, disease and aging can all cause bone injury. However, there is a lack of effective drugs against IDD and bone injury. Recent MSC-Exos finetuning has led to significant progress in the IDD treatment and bone repair and regeneration. In this review, we looked at the uniqueness of MSC-Exos, and the potential treatment mechanisms of MSC-Exos with respect to IDD, bone defects and injuries.